O corpo que come: comida, visualidade e turismo (Portugal, 1969-72) - Sampaio, Sofia (Trabalhos de Antropologia e Etnologia, 2020)
This article explores the potential of a visual anthropology of tourism, by analysing a visual object that has been largely neglected in both cinema studies and visual anthropology: the tourism promotional film. The object of analysis is the film Portugal Desconhecido [Unknown Portugal] (1969), which was made for the campaign that the Secretariat of State for Information and Tourism (SEIT) and the Tourism Head Office launched under the slogan: “There is always an unknown Portugal waiting for you”. Both the campaign and the film are indebted to the Portuguese State’s change of attitude towards tourism. The article concentrates on a sequence of images from the film that stood out in the corpus viewed, which offers some openings or “illuminations” into the study of the relationship between food and visuality in the Portuguese tourism context of the late 1960s.